2012
DOI: 10.3892/or.2012.1690
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression profile and differentially-expressed genes in prolactinomas following bromocriptine treatment

Abstract: Abstract.Little is known about the function of microRNAs in prolactinomas treated with bromocriptine. The aim of the study was to explore the microRNAs associated with bromocriptinetreated prolactinomas. Six prolactinoma samples were selected according to whether they received bromocriptine treatment or not before microsurgery, and microRNA expression profiles of bromocriptine-treated and untreated prolactinomas were screened by the miRCURY LNA Array. The differentially expressed microRNAs in microarrays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…Together with our results, these findings indicated that the deregulation of miR-550a could be common to several cancers and may have a functional role. Additionally, miR-550 has been found to be upregulated in prolactinomas following bromocriptine treatment [30]. Furthermore, miR-550 is among the eight microRNAs that predict sensitivity to prednisone in childhood acute lymphoblastic leukemia [29].…”
Section: Discussionmentioning
confidence: 99%
“…Together with our results, these findings indicated that the deregulation of miR-550a could be common to several cancers and may have a functional role. Additionally, miR-550 has been found to be upregulated in prolactinomas following bromocriptine treatment [30]. Furthermore, miR-550 is among the eight microRNAs that predict sensitivity to prednisone in childhood acute lymphoblastic leukemia [29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies based only on miRNA or mRNA expression profiles, examining both miRNA and mRNA expression profiles enables us not only to study miRNA and mRNA expression profiles separately but also to examine miRNA-mRNA regulatory pairs together [812]. Nevertheless, in many cancer studies based on miRNA and mRNA expression profiles, instead of considering miRNA-mRNA regulatory pairs together, the tendency is to examine either an miRNA or mRNA first and then apply strategies such as computational miRNA target gene prediction algorithms, sequence homology analysis, or expression correlation indexes to identify the corresponding counterpart of the miRNA (mRNA) and, hence, accomplish the integration of the miRNA-mRNA pair [12, 13]. Interestingly, many of these studies share the common assumption that the regulatory relationship between an miRNA and its target mRNAs is negative, and a great deal of research is therefore based on this assumption [812].…”
Section: Introductionmentioning
confidence: 99%
“…Total proteins from individual adult mice were extracted using radioimmunoassay protein extraction buffer system with protease/phosphatase inhibitors (Santa Cruz Biotechnology), denatured, separated on 12 % polyacrylamide gels and transferred to PVDF membranes (Bio- Rad) as described (Wang et al, 2015, Wang, Su, Sanai et al, 2012). Western blot analysis was performed by published methods (Wang et al, 2015, Wang et al, 2012) using primary antibodies specific to FSHβ (1:2,000; goat polyclonal antibody against human FSHβ), LHβ (1:2,000; goat polyclonal antibody against human LHβ ; Santa Cruz Biotechnology), β - tubulin (1: 2,000; rabbit polyclonal antibody, Santa Cruz Biotechnology) and appropriate secondary antibodies conjugated with HRP (Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed by published methods (Wang et al, 2015, Wang et al, 2012) using primary antibodies specific to FSHβ (1:2,000; goat polyclonal antibody against human FSHβ), LHβ (1:2,000; goat polyclonal antibody against human LHβ ; Santa Cruz Biotechnology), β - tubulin (1: 2,000; rabbit polyclonal antibody, Santa Cruz Biotechnology) and appropriate secondary antibodies conjugated with HRP (Santa Cruz Biotechnology). The antigen-antibody complexes were detected with an enhanced chemiluminescence kit (GE Healthcare) and the signals visualized on Biomax films (ISC Biosciences).…”
Section: Methodsmentioning
confidence: 99%